Beyond equilibrium thinking: dynamic area-based management tools in a changing ocean - Klerk, Bastiaan E.; Heinrich, Katharina; Primicerio, Raul (Frontiers in Marine Science, 2024)
Area-based management tools (ABMTs), including marine protected areas (MPAs) are often static and fail to reflect the dynamic realities of marine ecosystems. Marine ecosystems are characterized by their embodiment of constant change, which is further amplified by anthropogenic stressors, particularly climate change. ABMTs and MPAs are, however, premised on an implicit assumption of environmental equilibrium as their boundaries and management framework are often fixed and difficult to adjust. This article seeks to lay bare the tension between static conservation strategies and the deeply and inherently dynamic nature of marine ecosystems. It further seeks to advance the notion of dynamic ABMTs, proposing an integrated conceptualization of ABMT governance, one that is more apt to respond to the type of challenges that the dynamism of complex marine ecosystems presents. Dynamism, in this context, is broadly construed as encompassing three dimensions: spatial, with fluid and adjustable conservation measures; normative, denoting a volatile and adaptive management framework that utilizes ecological and management thresholds as an initiator for adaptive, timely, and prospective approaches to enhance management outcomes; and institutional, i.e., sufficiently flexible and dynamic institutional machinery overseeing ABMT implementation. Following a comprehensive conceptualization of dynamic ABMTs, the article addresses the question whether the legal frameworks governing the ocean can sustain such a dynamic mode of ocean governance.